Prevalence of Carbapenem-Resistant Klebsiella pneumoniae Co-Harboring blaKPC-Carrying Plasmid and pLVPK-Like Virulence Plasmid in Bloodstream Infections - Du, Fang-ling; Huang, Qi-sen; Wei, Dan-dan; Mei, Yan-fang; Long, Dan; Liao, Wen-jian; Wan, La-gen; Liu, Yang; Zhang, Wei (Frontiers in Cellular and Infection Microbiology, 2021)
This study aimed to characterize carbapenem-resistant Klebsiella pneumoniae (CR-KP) co-harboring blaKPC-2-carrying plasmid and pLVPK-like virulence plasmid. Between December 2017 and April 2018, 24 CR-KP isolates were recovered from 24 patients with bacteremia. The mortality was 66.7%. Pulsed-field gel electrophoresis and multilocus sequence typing results indicated four clusters, of which cluster A (n = 21, 87.5%) belonged to ST11 and the three remaining isolates (ST412, ST65, ST23) had different pulsotypes (cluster B, C, D). The blaKPC-2-carrying plasmids all belonged to IncFIIK type, and the size ranged from 100 to 390 kb. Nineteen strains (79.2%) had a 219-kb virulence plasmid possessed high similarity to pLVPK from CG43 with serotype K2. Two strains had a 224-kb virulence plasmid resembled plasmid pK2044 from K. pneumoniae NTUH-K2044(ST23). Moreover, three strains carried three different hybrid resistance- and virulence-encoding plasmids. Conjugation assays showed that both blaKPC-2 and rmpA2 genes could be successfully transferred to E. coli J53 in 62.5% of the strains at frequencies of 4.5 × 10−6 to 2.4 × 10−4, of which three co-transferred blaKPC-2 along with rmpA2 in large plasmids. Infection assays in the Galleria mellonella model demonstrated the virulence level of these isolates was found to be consistently higher than that of classic Klebsiella pneumoniae. In conclusion, CR-KP co-harboring blaKPC-2-carrying plasmid and pLVPK-like virulence plasmid were characterized by multi-drug resistance, enhanced virulence, and transferability, and should, therefore, be regarded as a real superbug that could pose a serious threat to public health. Hence, heightened efforts are urgently needed to avoid its co-transmission of the virulent plasmid (gene) and resistant plasmid (gene) in clinical isolates.